2018
DOI: 10.1016/j.stemcr.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

hPSC-Derived Striatal Cells Generated Using a Scalable 3D Hydrogel Promote Recovery in a Huntington Disease Mouse Model

Abstract: SummaryHuntington disease (HD) is an inherited, progressive neurological disorder characterized by degenerating striatal medium spiny neurons (MSNs). One promising approach for treating HD is cell replacement therapy, where lost cells are replaced by MSN progenitors derived from human pluripotent stem cells (hPSCs). While there has been remarkable progress in generating hPSC-derived MSNs, current production methods rely on two-dimensional culture systems that can include poorly defined components, limit scalab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 46 publications
0
55
0
Order By: Relevance
“…When injury or degeneration is so severe that a cavity has formed, or when glial cells themselves are significantly damaged, there will be a deficit of glial source to enact the conversion. In such severe injury condition, it may be necessary to transplant external cells to fill the cavity first for tissue repair 49 . Another limitation is for the treatment of diseases caused by gene mutations, such as the Htt mutation in R6/2 mouse model for HD used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…When injury or degeneration is so severe that a cavity has formed, or when glial cells themselves are significantly damaged, there will be a deficit of glial source to enact the conversion. In such severe injury condition, it may be necessary to transplant external cells to fill the cavity first for tissue repair 49 . Another limitation is for the treatment of diseases caused by gene mutations, such as the Htt mutation in R6/2 mouse model for HD used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The study results showed that the mice had reduced motor deficits as evidenced by reduced clasping and increased latency to fall from the rotarod. Moreover, the transplanted HD mice lived beyond their defined life span (∼19% increase) compared with the untreated, control mice . However, the transplanted cells in the HD brain contained mHTT aggregates in the nucleus, proving that the aggregates were transferred from the host cells to the transplanted cells.…”
Section: Stem‐cell‐based Therapy In Hd Rodent Modelsmentioning
confidence: 99%
“…Pluripotent-derived cells are amendable to organoid-based studies as they show capability of self-organization and have demonstrated the recapitulation of complex tissue architectures of the biliary tree (94), brain (95)(96)(97)(98), fallopian tube (99), intestine (100), liver (101,102), kidney (103), pancreas (104,105), retina (106)(107)(108)(109) and stomach (110). Such protocols have been applied to a host a genetic diseases including Alagille syndrome (111,112), autism (113), cystic fibrosis (94,112,114), enhanced scone syndrome (115), familial adenomatous polyposis (116), Huntington's disease (117), Leber congenital amaurosis (118), microcephaly (96), microlissencephaly (119), Miller-Dieker lissencephaly syndrome (120,121), polycystic kidney disease (122), retinitis pigmentosa (107)(108)(109), Rett syndrome (123,124) and Timothy syndrome (125). While these pluripotent-based organoids have yet to be heavily scaled they have been used as part of small-scale, targeted drug testing for Alagille syndrome (112), cystic fibrosis (94,112), familial adenomatous polyposis (116), polycystic liver disease (112) and Timothy syndrome (125).…”
Section: Recent Ipsc-based Drug Screening Effortsmentioning
confidence: 99%